RESTORATION OF ENDODONTICALLY TREATED TEETH: CLINICAL CHALLENGES AND SOLUTIONS - Lopez, Andres Santiago Quizhpi; Carvalho, Camila Nunes; Santos, Matheus Prates; Prates, Bruna Queiroz da Silva; de Melo, Maria Luisa Silva; Alves, Amanda Cypriano; Candido, Marco Antônio Teixeira (Seven Editora, 2026)
Endodontically treated teeth are more susceptible to fractures due to loss of tooth structure, biomechanical changes in dentin, and alterations in stress distribution. Rehabilitation of masticatory function after endodontic treatment is crucial for the long-term success of endodontic treatment and to prevent mechanical failures, such as coronal and root fractures, which can be common post-endodontics and jeopardize treatment success. This study aims to carefully review scientific works related to the most common challenges in clinical practice and restorative solutions for endodontically treated teeth, focusing on the amount of remaining tooth structure, dental cavity, and selection of restorative material related to fracture resistance and clinical outcome. The literature review was based on evidence from systematic reviews, randomized clinical trials, and laboratory studies, discussing both direct and indirect restorations, fiber-reinforced composites, adhesive partial restorations, and factors related to the risk of vertical root fractures. The studies used as a reference for this article show that preserving as much of the remaining tooth structure as possible is the main point for the success of the treatment. Fiber-reinforced restorative materials tend to show greater resistance to fracture and consequently to treatment failure when compared to conventional restorative materials in in vitro studies, although clinical evidence still presents limitations. Adhesive indirect partial restorations, especially those with cusp coverage, show better clinical performance when compared to more conservative ones in endodontically treated posterior teeth. In conclusion, the choice of the best restorative technique should be individualized, taking into account the presence and amount of remaining tooth structure, the occlusal characteristics of the tooth, the risk of fracture, and the biomechanical characteristics of the previously endodontically treated tooth. Minimally invasive restorative techniques associated with more modern adhesive materials show a promising strategy, even though long-term clinical studies are still needed to strengthen evidence-based recommendations. DOI: https://doi.org/10.56238/sevened2026.003-005